2023
DOI: 10.1002/ppul.26434
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric respiratory admissions and related viral infections during the COVID‐19 pandemic

Abstract: Introduction:The COVID-19 pandemic has affected the incidence of respiratory viral infections. Our aim was to assess changes in pediatric admissions due to respiratory diseases and associated respiratory viral infections.Methods: An observational study including all respiratory admissions to the pediatric departments from January 2015 to August 2021. We compared respiratory admission percentage, respiratory viral panel results and clinical characteristics of these admissions between two study periods, January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
(88 reference statements)
0
9
0
Order By: Relevance
“…An atypical summer spike in RSV in 2021 followed, which is likely the primary driver in the increased bronchiolitis visits, both features seen in other studies. 13,[17][18][19]27 The summer ED visits that year were almost as high as the winter of the last typical season in 2019, though there was a bimodal distribution with an increase in the winter months though lower than the summer surge, suggesting there is still some seasonality During the low volume year of 2020, rhino/enterovirus was the predominant virus detected by percentage, though the raw number detected was relatively similar to previous years. It is possible that more rhinovirus was detected due to higher testing rates, which increased by 23% from the year prior.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…An atypical summer spike in RSV in 2021 followed, which is likely the primary driver in the increased bronchiolitis visits, both features seen in other studies. 13,[17][18][19]27 The summer ED visits that year were almost as high as the winter of the last typical season in 2019, though there was a bimodal distribution with an increase in the winter months though lower than the summer surge, suggesting there is still some seasonality During the low volume year of 2020, rhino/enterovirus was the predominant virus detected by percentage, though the raw number detected was relatively similar to previous years. It is possible that more rhinovirus was detected due to higher testing rates, which increased by 23% from the year prior.…”
Section: Discussionmentioning
confidence: 81%
“…Another study reported no change in admissions for wheezing at this time. 13 The dominance of rhino/enterovirus during the emergence of the pandemic and the disappearance of RSV raises important questions about how the transmission of this virus was affected by efforts to slow the spread of COVID-19. RSV is an enveloped, singlestranded, negative-sense RNA virus of the Pneumoviridae family and is transmitted via droplet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the nearly 3-year-long COVID-19 pandemic, unprecedented attempts have been made worldwide to prevent infection, and both children and adults have been encouraged to wear masks, wash their hands, and keep their distance from others. 1 , 13 In Japan, children in kindergartens and elementary and junior high schools have been forced to limit class hours and change class formats over a long period of time. 14 Thus, it is speculated that these actions significantly reduced the prevalence of respiratory tract infections in children during the pandemic.…”
Section: Discussionmentioning
confidence: 99%